Integrated study of lithofacies identificationâa case study in X field, Sabah, Malaysia - Ngui, J.Q. (MDPI AG, 2018)
Understanding subsurface geology is essential for oil and gas exploration. Seismic facies interpretation is very useful in investigating this concept. The interpretation of the depositional setting of the X Field is achieved by integrating the seismic facies characteristics on 3D seismic data and well log data. Both the seismic and well log data are widely used in hydrocarbon exploration to map the subsurface, as they complement each other. Well logs yield the vertical resolution of the subsurface geology at the drilled well, whereas seismic data reveal the lateral continuity. The objective of this paper is to demonstrate the integration of 3D seismic data and well log data for lithofacies identification. Interpretation and analysis of lithofacies is carried out through the integration of the characteristics of seismic reflections with well information (logs). Horizons are interpreted based on the variation in seismic reflections on the seismic section, which is caused by the change in geology within seismic sequences. Well logs give detailed information at the points where the wells were drilled. Interpolating between these points and extrapolating away from the points into undrilled areas can be helpful in providing a better geological knowledge of an area. The result of this integrated study depicts the lithofacies in the area. This integrated study will provide a better insight with higher degree of reliability to the facies distribution and depositional setting of the X Field. The geological and geophysical aspects of the field will be documented. Â© 2018 by the authors.